Numerical Simulation of non-Newtonian Fluid Flows through Fracture Network. (January 2016) - Dharmawan, I A; Ulhag, R Z; Endyana, C; Aufaristama, M
Abstract: We present a numerical simulation of non-Newtonian fluid flow in a twodimensional fracture network. The fracture is having constant mean aperture and bounded with Hurst exponent surfaces. The non-Newtonian rheology behaviour of the fluid is described using the Power-Law model. The lattice Boltzmann method is employed to calculate the solutions for non-Newtonian flow in finite Reynolds number. We use a constant force to drive the fluid within the fracture, while the bounceback rules and periodic boundary conditions are applied for the fluid-solid interaction and inflow outlflow boundary conditions, respectively. The validation study of the simulation is done via parallel plate flow simulation and the results demonstrated good agreement with the analytical solution. In addition, the fluid flow properties within the fracture network follow the relationships of power law fluid while the errors are becoming larger if the fluid more shear thinning.